Educational and cultural programming in the first channel in Colima: XHCC TV Channel 5-Televisión de Colima (1960-1966) - Chavez Chapa, Esmirna; Fernández Reyes , Amaury (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
With the arrival of the first television channel in Colima, XHCC TV Channel 5-Televisión de Colima, the foundations were laid for the establishment of this technological invention in the region, since it was a very important cultural event for the mass media, being the first television channel in the state of Colima. Among the greatest contributions of the company Televisión de Colima, S.A., was to put it into operation as a tool for educational and cultural outreach, since programming of this nature was a pillar for its promotion, the refore, we consider that it has been a little-studied phenomenon so far but necessary to address. This work is located within the studies related to the history of regional media and educational television, and integrates part of an exploratory documentary research work, based on the review of bibliographic and photographic documents, from the use of techniques such as documentary review, through qualitative-interpretative content analysis and interviews.